Estudo comparativo entre semicondutores de silício e nitreto de gálio em circuitos de acionamento de leds - Duarte, Renan Rodrigo (2017)
This dissertation presents a comparative study about the performance of silicon (Si) and gallium nitride (GaN) semiconductors in drivers for light emitting diodes. Hereby, it is expected to provide the theoretical background required for the development of future works using this new technology. Theoretical aspects related to the materials used in the manufacture of semiconductors and their implications in the final product, as well as the characteristics and peculiarities of GaN semiconductors are presented. The experimental development consisted of two case studies, each focused on a distinct topology with different types of GaN semiconductors. First, a comparison of Si and enhancement mode GaN transistors was carried out in a family of synchronous buck converters. Ten 48 V to 28.3 V and 22.6 W converters were designed with the same parameters, at five different switching frequencies, ranging from 100 kHz to 1 MHz. Efficiency and temperatures were measured in four different scenarios: with and without an external diode in parallel with the low-side switch and with two different dead-time values, 25 ns and 50 ns. Converters with GaN transistors showed higher efficiency and lower temperatures in all cases, with a maximum efficiency of 96.8% and a minimum of 94.5%. In addition, Si-based converters exhibited greater performance degradation as the switching frequency and dead time increased. In the second study, nine 75 W off-line integrated double buck-boost converters were developed and evaluated. Two different Si technologies were compared with a cascode GaN transistor at three switching frequencies, ranging from 50 to 150 kHz. Again, the efficiency and temperatures of the prototypes were measured. The converters with GaN demonstrated superior performance in all cases, yielding about 5% gain in efficiency over the worst tested Si semiconductor. In both cases, the converters’ loss distribution was presented based on simulation results. It was concluded that the gallium nitride transistors have the potential to replace silicon technology mainly due to its superior performance and requirement of small, or no change, in the original circuit.